2018
DOI: 10.2147/hiv.s159670
|View full text |Cite
|
Sign up to set email alerts
|

Risky sexual behavior and associated factors among antiretroviral therapy attendees in Nekemte Referral Hospital, Western Ethiopia: a cross-sectional study

Abstract: BackgroundHIV/AIDS remains a major public health problem. Practice of risky sexual behaviors is the major effective driver of the HIV epidemic among HIV-positive individuals. This behavior exposes their partners to HIV, and for those that are already positive it exposes them to a risk of suprainfection by other strains.ObjectiveThe aim of this study was to assess the prevalence of risky sexual behavior and associated factors among people living with HIV attending antiretroviral therapy (ART) clinic at Nekemte … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 17 publications
(30 reference statements)
9
22
0
Order By: Relevance
“…The findings of this study are consistent with the findings of similar studies conducted in comparable settings (20,21). The fact that women who talked about condoms with partner during the preceding 12 months were more likely to use condoms during their sexual encounter suggests that being in a relationship where women are confident to have discussions related to sexual practices with their partners, is important for improving women's confidence to negotiate for condom use.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The findings of this study are consistent with the findings of similar studies conducted in comparable settings (20,21). The fact that women who talked about condoms with partner during the preceding 12 months were more likely to use condoms during their sexual encounter suggests that being in a relationship where women are confident to have discussions related to sexual practices with their partners, is important for improving women's confidence to negotiate for condom use.…”
Section: Discussionsupporting
confidence: 88%
“…Although this study did not precisely focus on contraceptive use, linking these behavioural changing patterns among women is important, given the concerns they are raising. Similar to this study, risky sexual behaviours among participants whose partners were HIV positive was also shown in Ethiopia (21). There is less chances of condom use at sexual debut among youth (7,23), suggesting the importance of delaying sexual debut among women until they are able to make the informed and/or guided decisions with full considerations of the exposure to HIV infection (24).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Although this study did not precisely focus on contraceptive use, linking these behavioural changing patterns among women is important, given the concerns they are raising. Similar to this study, risky sexual behaviours among participants whose partners were HIV positive was also shown in Ethiopia [22]. There is less chances of condom use at sexual debut among youth [3,24], suggesting the importance of delaying sexual debut among women until they are able to make the informed and/or guided decisions with full considerations of the exposure to HIV infection [25].…”
Section: Discussionsupporting
confidence: 72%
“…Despite some similar findings to a study conducted in Tanzania, some aspects are contradictory, in as far as the associations between condom use and multiple sexual partners among women are concerned [21]. However, in Ethiopia, participants who were on antiretroviral therapy (ART) and had multiple sexual partners were more likely to engage in risky sexual behaviour [22], and this pattern was observed in both males and females alike. In this study, we found no evidence to suggest that HIV positive status of women had any significant influence on condom use in multivariate analysis.…”
Section: Discussionmentioning
confidence: 82%